Pengaruh Kemandirian Belajar, Kecerdasan Emosional, Teman Sebaya, Penggunaan Media Pembelajaran, dan Fasilitas Belajar terhadap Hasil Belajar Siswa Kelas X pada Mata Pelajaran Ekonomi di SMAN 1 Kuantan Hilir - Saprilla Saprilla; Sri Wahyuni; Jimi Ronald (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
This study analyzes the effects of learning independence, emotional intelligence, peers, learning media usage, and learning facilities on students’ learning outcomes, both partially and simultaneously. Using an associative research design, the study was conducted in July 2026 at SMAN 1 Kuantan Hilir. The population comprised all Grade X students taking Economics, with a sample of 132 students selected through proportional random sampling. Data were analyzed using descriptive and inductive techniques with EViews and SPSS version 21.0. The results show that learning independence significantly affects learning outcomes, with a coefficient of -0.909, t-value of 10.695 > 1.65704, and significance of 0.000. Emotional intelligence has a significant positive effect, with a coefficient of 0.250 (t = 3.797; p = 0.000). Peers also have a significant positive effect, with a coefficient of 0.338 (t = 3.829; p = 0.000). Learning media usage significantly affects outcomes, with a coefficient of 0.309 (t = 3.950; p = 0.000), while learning facilities show a positive effect with a coefficient of 0.380 (t = 4.982; p = 0.000). Simultaneously, all five variables significantly affect learning outcomes, as indicated by F-value of 29.600 > 2.28.